THE STRATEGY OF ESTABLISHING A CONTACT IN INTERVIEW GENRE (BASED ON A. MERKEL TALK WITH “BRIGITTE” MAGAZINE) (Proceedings of Southern Federal University. Philology, 2014)
Key words: discourse, text, communication, double addressee, strategy, tactic.In this article the discourse and the text are considered from the communicative approach viewpoint. The discourse is formed in a set of genres inherent in it, each has the genre signs characterizing the text as a whole, allowing to correlate each separate text to this or that genre within a definite discourse. The basic feature of a journalistic discourse is in double addressing: an interviewee and a reader (the second addressee). Communicative strategies of the interview represent the mechanisms promoting efficiency of communication between the sender and the addressee. Cooperation as the global objectives of interview is achieved through the strategy of establishing the contact or rapprochement strategy. Ways of realization of this strategy are tactics aimed at bringing the interviewer, the interviewee and the reader closer.Neshenko Anna Vladimirovna - candidate of linguistics, senior lecturer.